Islamic Left Manifesto: Hasan Hanafi and Interpretation of Materialism on Islamic Tradition - Sayuti, Sayuti; Inayatillah, Inayatillah (Sekolah Tinggi Agama Islam Taruna Surabaya, 2025)
The challenge of integrating a materialist approach into Islamic interpretation is generally spiritual and theological. Hasan Hanafi's thoughts, which promote left-wing Islam, present an ideological conflict, especially with traditional interpretations that focus more on aspects of faith and spirituality. This study uses library research because the primary focus of the study is on collecting secondary data through a study of various written literature sources. The study results show that: 1) Hasan Hanafi's Islamic Leftic Concept influences the interpretation of materialism in the Islamic tradition. Hasan Hanafi developed the concept of Islamic Left, which integrates the ideology of materialism with Islamic principles. In his thinking, Islam is not only seen as a spiritual religion, but also as a tool to criticize social and political injustice, and to encourage structural change. 2) The implications of the interpretation of materialism according to Hasan Hanafi in contemporary Islamic thought are that Hanafi's materialist interpretation brings important implications in contemporary Islamic thought by emphasizing that religious texts must be understood in a social and economic context. He argues that Islam must function as a force for social change, not just for individual worship. 3) The problems of Hasan Hanafi's thinking and the interpretation of materialism according to the views of Muslim intellectuals are that Hasan Hanafi's thinking on the interpretation of materialism faces criticism from conservative Muslim intellectuals who consider it a deviation from traditional interpretation.